"Text It" program to track falls in patients with Alzheimer's disease and dementia. Issue 1 (7th April 2018) - Kamil, Rebecca J.; Bakar, Dara; Ehrenburg, Matthew; Frankenthaler, Scott; Wei, Eric X.; Anson, Eric; Oh, Esther; Agrawal, Yuri
Abstract: Introduction: Falls are a significant problem among older adults with Alzheimer's disease, leading to high rates of fracture, hospitalization, and death. Tracking falls in older adults, particularly those with cognitive impairment, is a clinical and research challenge. Methods: This prospective pilot study evaluated the feasibility of a text message program to track falls among patients with dementia. We also compared this technique with the calendar method of fall data collection. Results: There was a 96% completion rate of text messaging and 100% of calendars; however, the text‐gathered data were more accurate. Discussion: A text‐messaging platform to track falls shows promise in cognitively impaired individuals.